All we expect nutrition : a basic human right [videorecording] - Micronutrient Initiative (Ottawa, Ontario Micronutrient Initiative, 1995)
Describes the significance of micronutrient malnutrition, especially as it affects women. Outlines the effects of iron, iodine, and vitamin A deficiencies and provides examples of how to overcome them.
Narrator, Gabrielle Hezekiah ; participants, Pamela Chabikwa, Talent Mucheri.
Keywords: Trace elements in nutrition; Women -- Nutrition -- Developing countries